Improving End-User Satisfaction with Electronic Medical Records (EMR) - Agiwahyuanto, Faik; Suyoko, Suyoko; Anjani, Sylvia; Wulandari, Fitria (Puslatbang KDOD Lembaga Administrasi Negara, 2025)
In today's interconnected world, it is widely understood that the effectiveness of health information system, a key component of information technology, depends on user satisfaction. In theory, electronic medical records (EMRs) were just a substitute for paper records; nevertheless, they have brought about substantial changes to the working circumstances of nurses and other professionals in the healthcare business. This study introduces a novel approach to improve user satisfaction within Semarang City context, which could potentially be implemented globally. The impact of modern technology was investigated by applying Aggelidis and Chatzouglou's End User Computing Satisfaction (EUCS) approaches to previous health information system (HIS). As a result, the fundamental model was enhanced by including a new factor known as